Menurunkan Keluhan Nyeri Punggung Bawah Pada Guru Sma Melalui Edukasi Peregangan Otot Di Tempat Kerja - Widya Andini; Chairul Ichsan; Agus Joko Susanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Teachers are one of the groups at high risk of experiencing lower back pain (LBP). Teachers often experience lower back pain due to static sitting or working positions, which can trigger repetitive strain injuries. Community service aims to identify efforts to prevent and treat lower back pain in teachers. The method used is a quantitative approach by looking at the effects before and after education is given. The results of activities for SMAN 10 teachers showed a decrease in the average complaint of lower back pain before education was given 5.9 and after becoming 2.3, it was proven to be effective in overcoming the problem of lower back pain disorders